Pelatihan Literasi Digital sebagai Upaya Penanggulangan Hoaks - Andriani, Astri Dwi (Jurnal Media Pengabdian Komunikasi, 2023)
Abstract The rapid development of information technology has made internet growth in Indonesia accelerate very quickly. APJII and We are Social noted that in 2023 the number of internet users in Indonesia will reach 215 million users with a duration of 8.5 hours per day. One of the biggest challenges faced in the current digital era is the spread of hoaxes on social media. Realizing that hoaxes are a real threat to Indonesian society, the government through the Ministry of Communication and Information of the Republic of Indonesia in 2021 took preventive steps, namely launching a digital literacy movement for 12.4 million people in 34 provinces. One of the locations chosen to carry out digital literacy activities is Pidie Regency, Aceh, Sumatra. Digital literacy is considered absolutely necessary so that new media (the internet) truly brings benefits to its users. The aim of this research is to expose the public to knowledge about digital literacy. The digital literacy activities carried out in Pidie Regency, Aceh, Sumatra were carried out online via a seminar or webinar website on May 25 2023. The webinar was presented using several methods, namely the lecture method, discussion method, question and answer method, and simulation and practice. The contribution of this community service was that 427 participants were exposed to information about digital literacy from students from Pidie Regency, Aceh, Sumatra. It is hoped that this activity can lead the people of Pidie Regency to become a literate society. Keywords: Digital; literation; hoax.   AbstrakPesatnya perkembangan teknologi informasi membuat pertumbuhan internet di Indonesia melaju begitu cepat. APJII dan We are Social mencatat bahwa tahun 2023 jumlah pengguna internet di Indonesia menember 215 juta pengguna dengan durasi 8,5 jam per hari. Salah satu tantangan terbesar yang dihadapi di era digital saat ini adalah penyebaran hoaks di media sosial. Menyadari bahwa hoaks merupakan ancaman nyata bagi masyarakat Indonesia, pemerintah melalui Kementerian Komunikasi dan Informatika Republik Indonesia pada tahun 2021 melakukan langkah preventif, yaitu mencanangkan gerakan literasi digital untuk 12,4 juta rakyat di 34 provinsi. Salah satu lokasi yang dipilih untuk melaksanakan kegiatan literasi digital adalah KabupatenPidie, Aceh, Sumatera. Literasi digital dianggap mutlak diberikan agar media baru (internet) benar-benar menghadirkan  manfaat  bagi  penggunanya. Tujuan dari pengabdian ini adalah untuk membuat masyarakat terpapar pengetahuan mengenai literasi digital. Adapun kegiatan literasi digital yang dilakukan di Kabupaten Pidie, Aceh, Sumatera ini dilakukan secara daring atau online melalui website seminar atau webinar pada tanggal 25 Mei 2023. Webinar disajikan dengan menggunakan beberapa metode, yakni metode ceramah, metode diskusi, metode tanya jawab, serta metode simulasi dan praktek. Kontribusi dari pengabdian kepada masyarakat ini adalah sebanyak 427 peserta terpapar informasi mengenai literasi digital yang berasal dari kalangan pelajar Kabupaten Pidie, Aceh, Sumatera. Diharapkan kegiatan ini bisa mengantarkan masyarakat Kabupaten Pidie menjadi masyarakat yang literat.  Kata-kata kunci:  Digital; literasi; hoaks.